Willingness To Pay Sampah di Kota Berkembang: Studi Kasus Kota Meureudu Provinsi Aceh, Indonesia: Willingness To Pay For A Waste Management In A Developing Town: Case Study Of Meureudu City, Aceh Province, Indonesia - Nurul Muhshanati; Cut Azizah; Rahmat Abbas (LPPM Universitas Mataram, 2023)
Waste become one of the undermined issues faced in many countries, including Indonesia. Meureudu City in Aceh Province, Indonesia, is currently under development process to optimize its waste management. The waste issue in the city originated from the insufficient waste retribution cost. This study aims to analyze Willingness to Pay (WTP) in the case of waste generation. We use a survey method by conducting field observation with the community of Meureudu City as our sample, which amounted to 110 respondents. Our study showed that female housewife is the main gender in household waste management. Factors of the age group of 31-40 years (35%), bachelor and diploma education level (42%), high income, and family member > 4 persons (28%) are affecting the WTP. We also managed to gather information on the average waste of Meureudu City which amounted to 1,5 kg/person/day, exceeding the Ministerial Law of Environmental and Forestry (0,7 kg/person/day). Our study revealed the average WTP for waste management by the community of Mereudu City is IDR 9.218,18/household, which is higher compared to the regulated retribution cost. These additional costs will be beneficial to improve better waste management.